PELAKSANAAN PUBLIC RELATION DALAM PEMBUATAN SIM DI SATUAN LALU LINTAS POLRES SUMEDANG - Dede Sela Puspitasari (LPPM UNSAP, 2026)
This study aims to examine the implementation of public relations in the issuance of driving licenses (SIM) at the Traffic Unit of Sumedang Police Department, identify the inhibiting factors, and explore the efforts made to overcome these obstacles. A qualitative descriptive method was employed, using data collection techniques such as observation, interviews, and documentation. The findings reveal that public relations activities have been carried out through information dissemination and communication with the public. However, several challenges remain, including unclear information, limited technological facilities, and underutilized communication media. The main inhibiting factors include inadequate infrastructure, ineffective communication techniques, and unsupportive physical or environmental conditions. To address these issues, the institution has made efforts such as enhancing human resource competencies, improving facilities, and developing more effective communication channels. Effective public relations practices are expected to improve public service delivery and foster a positive image of the police institution among the community.